2019
DOI: 10.1007/s00431-019-03334-7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational well-being in pediatricians—a survey about work-related posttraumatic stress, depression, and anxiety

Abstract: The objective of this study was to study mental health, coping, and support after work-related adverse events among pediatricians. Physicians are frequently exposed to adverse events. It makes them at risk for posttraumatic stress disorder (PTSD), depression, and anxiety disorders. Besides the personal impact, physicians could pose a threat towards patients, as mental health problems are associated with medical errors. A questionnaire was sent to all members of the Pediatric Association of The Netherlands in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
0
36
1
1
Order By: Relevance
“…In conclusion, since trauma and PTSS are common (Kessler et al, 2017) and considered a public health issue (Magruder, McLaughlin, & Elmore Borbon, 2017), there is an urgent need to explore how to deliver easy-accessible evidence-based interventions to individuals affected by trauma. Self-help apps could be useful to assess trauma-related symptoms and resilience (van der Meer, Bakker, Schrieken, Hoofwijk, & Olff, 2017), to monitor mental health symptoms during the acute post-trauma period, to reduce these symptoms, and possibly prevent them (Kuhn et al, 2018;Olff, 2015). Our study suggests that SUPPORT Coach may potentially provide easy-accessible low-intensity self-help to empower individuals following trauma and reduce (subclinical) negative trauma-related consequences.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In conclusion, since trauma and PTSS are common (Kessler et al, 2017) and considered a public health issue (Magruder, McLaughlin, & Elmore Borbon, 2017), there is an urgent need to explore how to deliver easy-accessible evidence-based interventions to individuals affected by trauma. Self-help apps could be useful to assess trauma-related symptoms and resilience (van der Meer, Bakker, Schrieken, Hoofwijk, & Olff, 2017), to monitor mental health symptoms during the acute post-trauma period, to reduce these symptoms, and possibly prevent them (Kuhn et al, 2018;Olff, 2015). Our study suggests that SUPPORT Coach may potentially provide easy-accessible low-intensity self-help to empower individuals following trauma and reduce (subclinical) negative trauma-related consequences.…”
Section: Discussionmentioning
confidence: 85%
“…Although PTSS decline gradually in the majority of people and are less impairing than full-blown PTSD, they nevertheless cause distress and are associated with depression, alcohol use, and limitations in occupational and social functioning (Cukor, Wyka, Jayasinghe, & Difede, 2010;Marshall et al, 2001). Moreover, individuals with PTSS are at increased risk of developing (delayed) PTSD, especially after experiencing subsequent PTEs or other stressors (Smid, Mooren, van der Mast, Gersons, & Kleber, 2009). This heightened chance to develop (delayed) PTSD may particularly apply to high-risk professions such as health care professionals (HCPs), who are regularly exposed to work-related trauma (De Boer et al, 2011;van Steijn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the potentially adverse effects of intranasal OT on mood and the increased fear processing and reduced top-down control over amygdala activation in women with acute trauma exposure warrant cautionary use of intranasal OT in postpartum women. For acutely traumatized postpartum women, preventive interventions that aim at social (i.e., partner) and obstetric staff support in order to further promote endogenous oxytocin release may be more beneficial in preventing PTSD-FC (van Heumen et al 2018;van Steijn et al 2019). Finally, because individual and situational circumstances matter, future clinical research trials that provide possibilities to examine the more individualized therapeutic response of exogenous OT, for example by using personalized methods, might give directions on who will obtain most benefit from exogenous OT.…”
Section: Clinical Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…The first from Israel showed a 33% burnout rate among paediatricians, especially those ‘salaried, young, and working long hours’ . The second paper from the Netherlands found that 79% of paediatricians surveyed experienced adverse events, the most common being ‘aggressive behaviour’ and the most distressing being ‘a misdiagnosis’ . Of the paediatricians, 7.3 and 14.1%, respectively, scored above the cut‐off points for depression and anxiety, while 2.2% scored within the post‐traumatic stress disorder range.…”
mentioning
confidence: 99%